Effect of oxygen on some reactions of ZnSe crystal surface interaction with H₂O vapors, CO₂, and CO - Gal'chinetskii, L.P.; Galkin, S.N.; Dobrotvorskaya, M.V.; Rybalka, I.A. (Functional Materials, 2012)
Effect of oxygen on some interaction reactions of ZnSe crystal surface with water vapors, CO₂, and CO which result in release of hydrogen, and also carbon from a surface of crystals is discussed. Temperature dependences of equilibrium constants are calculated. It is found that participation of oxygen into the viewed processes of interacting results in sharp increase of probability and intensity of their actual behavior. It was shown that the essential contribution to these processes can be made by presence of antropogenic admixtures in air (water, hydrocarbons, CO₂, CO, engine exhaust fumes, etc.) which plays a critical part in pollution of ZnSe crystals surface by carbon.